2018
DOI: 10.1007/s11356-018-1560-y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of organics from aqueous phase by acid-activated coal fly ash: preparation, adsorption, and Fenton regenerative valorization of “spent” adsorbent

Abstract: Raw coal fly ash was activated to an adsorbent by sulfuric acid impregnation. The activation condition, the adsorption capacity, and the regenerative valorization of the adsorbent were studied. The results show that the optimal preparation conditions of the adsorbent are [HSO] = 1 mol L, activation time = 30 min, the ratio of coal fly ash to acid = 1:20 (g:mL), calcination temperature = 100 °C. The adsorption of p-nitrophenol on the adsorbent accords with the pseudo-second-order kinetic equation and the adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…One significant observation is that the results of XRD analysis revealed that quartz (Q) presents the highest intensity—mullite (M) and hematite (He); the mainly crystalline phases of the unmodified fly ash [ 26 ] can also be identified in FA/H 2 SO 4 . Additionally, FA/H 2 SO 4 shows a prominent peak at 2 theta = 25.63° that can be attributed to modernite (MOR)[Na 8 (H 2 O) 24 ] [Si 40 Al 8 O 96 ] [ 35 , 36 ]. In the case of FA/H 2 SO 4 +Cd 2+ the peaks can be observed in minor intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One significant observation is that the results of XRD analysis revealed that quartz (Q) presents the highest intensity—mullite (M) and hematite (He); the mainly crystalline phases of the unmodified fly ash [ 26 ] can also be identified in FA/H 2 SO 4 . Additionally, FA/H 2 SO 4 shows a prominent peak at 2 theta = 25.63° that can be attributed to modernite (MOR)[Na 8 (H 2 O) 24 ] [Si 40 Al 8 O 96 ] [ 35 , 36 ]. In the case of FA/H 2 SO 4 +Cd 2+ the peaks can be observed in minor intensity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, after Cd 2+ adsorption there was a shift in the bands between 1700 cm −1 and 400 cm −1 , which proves the adsorption process of Cd 2+ on the FA/H 2 SO 4 sample [33,34]. One significant observation is that the results of XRD analysis revealed that quartz (Q) presents the highest intensity-mullite (M) and hematite (He); the mainly crystalline phases of the unmodified fly ash [26] [35,36]. In the case of FA/H 2 SO 4 +Cd 2+ the peaks can be observed in minor intensity.…”
Section: Ftir Analysismentioning
confidence: 99%
“…Therefore, the combination of photocatalysts and highly efficient adsorbent materials to achieve adsorptionphotocatalytic "cooperation" can also effectively increase photocatalytic efficiency. Currently, the use of waste materials to prepare new, inexpensive, "green" adsorbents is a hot topic of research (Abbas 2014;Jiang et al, 2018), such as quartz particles, fly ash, zeolite and other natural materials and waste slag-based adsorbent materials (Cao et al, 2018;Wang et al, 2018;Alvarez-García et al, 2019). The oyster is a highly productive and environmentally adaptable aquatic organism that absorbs elements from the surrounding environment and forms a shell with a carbonate composition through the secretion of its soft body, rich in CaCO 3 and a large number of micropores.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorbent may adsorb a large number of organic pollutant molecules, thus facilitating the reaction between the organic molecules and the active radicals formed on the TiO 2 surface, forming an adsorption-catalysis photodegradation pathway. Currently, the use of waste materials to prepare new, inexpensive, "green" adsorbents is a hot research topic [14] [15], such as quartz particles, fly ash, zeolite, and other natural materials and waste residue-based adsorbent materials [16] [17] [18] [19]. However, there are not many reports on the preparation of composite photocatalysts with adsorption-photocatalytic synergy by combining the above-mentioned types of adsorbent materials with modified TiO 2 .…”
Section: Introductionmentioning
confidence: 99%